"Validación de un instrumento para medir la calidad de vida de la clase media dela ciudad de Quito". - Paredes Núñez, Silvana Noemí (2013)
Contains desarrolllo a methodology focused on the validation of an instrument to measure quality of life in the middle class of the city of Quito where desarrolllo and application of different statistical coefficients is performed aimed at ensuring the reliability and validity of this instrument through the development of a clearly established procedure to ensure that the data collected through this mechanism are valid.